INDEKS MAQASHID SYARIAH DAN NILAI PERUSAHAAN BANK UMUM SYARIAH - Hidayat, Rida Almiravalda; Usman, Usman (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Islamic banks require a different performance measurement than a conventional bank to keep their sustainability. The main disadvantage of employing conventional benchmarks to measure Islamic bank performance is that they fail to investigate shariah facets. This study aims to discover how maqashid shariah index using IMSPM (Integrated Maqashid al-Shariah based Performance Measure) approach and firm value using EVA (Economic Value Added) approach and examine its impact with capital structure on the corporate values of Islamic bank. This study using a quantitative method with the purposive sampling technique. This study involved 11 Islamic bankâ€™s annual reports listed in the Bank Indonesia and OJK from 2015 to 2019 period. The analysis method is multiple linear regression using Eviews 10 program. This study finds that the sample performed highest on the objective of nafs (self) over five-year period. The companies with a constant NOPAT and IC have a better EVA. Maqashid Syariah Index positively influence firm value while the capital structure has no effect.Â